A cone beam computed tomographic study on sphenoid sinus pneumatization - Karthikeya Patil; C J Sanjay; Mahima V Guledgud; K R Renuka Devi; Namrata Suresh; Eswari Solayappan (Wolters Kluwer Medknow Publications, 2023)
Background: Variations in pneumatization. of the sphenoid sinus can affect suprasellar, parasellar, and middle cranial fossa procedures. A 3-D imaging modality, like cone beam computed tomography (CBCT), overcomes superimpositions and magnification to provide an efficient evaluation of anatomical components across multiple planes. Objective: The purpose of this study is to conduct an epidemiological assessment inspired by the classifications provided by Gibelli et al. and Bilgir et al. on the morphological variants of the sphenoid sinus pneumatization using CBCT in a South Indian population. Materials and Methods: Around 154 CBCT images of sphenoid sinuses devoid of pathologies were examined. Descriptive analysis and Pearson Chi-square test were evaluated using SPSS 22.0 software. Results: Patients had a prevalence of 5.84% presellar, 27.2% sellar, and 51.9% postsellar posteroanterior pneumatization but no conchal pneumatization. About 14.2% showed aberrant pneumatization involving the pterygoid, anterior clinoid, and dorsum sellae. Conclusion: A thorough understanding of surgical anatomy and its variances is necessary to perform surgery with minimal possibility of human error and morbidity. To achieve this, a comprehensive classification of sphenoid sinus pneumatization is required as there is a disparity among the various study results presented in the previous literature.